Pengaruh Social Media Content Marketing Dan Brand Perception Terhadap Purchase Intention Produk “Es Teh Indonesia” - Marzata, Dera; Tiarawati, Monika (Peneliti.net, 2023)
Es Teh Indonesia reaching its customers by uploading a variety of marketing content on social media platforms, but throughout 2022 this content has become controversial in terms of the attitude policy taken by Es Teh Indonesia and how the company maintains relationship with its customers to the point of causing various perceptions that influence purchase intentions, especially among potential consumers. The purpose of this study was to determine the effect of Social Media Content Marketing and Brand Perception on Purchase Intention for Es Teh Indonesia’s products. This study used a quantitative method with a causal conclusive research model, using non-probability sampling and purposive sampling techniques. Questionnaires were distributed online to 220 respondents using a Likert scale of 1-5. The results showed that there was a significant influence between Social Media Content Marketing and Brand Perception on Purchase Intention for Es Teh Indonesia Products. Companies must consider what kind of content can shape perceptions that can lead to purchase intentions for Es Teh Indonesia’s products.